Financing innovation: The role of patent examination - Stephen D. Billington; Christopher L. Colvin; Christopher Coyle (Queen's University Centre for Economic History (QUCEH), 2025)
How does patent examination influence access to finance for innovative firms? We exploit a reform to the UK's patent system that introduced substantive examination to the patent application process, improving the information available to potential investors on the value of firms' patents. Using a newly compiled firm-level dataset of exchange-listed corporations, we find that firms holding examined patents were able to borrow more, reflecting improved access to capital markets, and leading to firm growth. Our results highlight the role of patent examination in reducing information asymmetries, enhancing the signalling value of patents, and mitigating financial barriers to innovation.
Keywords: G32; N23; N43; O16; O31; O34; 330; firm finance; debt; innovation; patents; patent examination; signalling